Man as Microcosm in Renaissance Philosophy - Jonkus, Dalius (Problemos, 1994)
Based upon the analysis of the theories of Nicolas of Cusa and Paracelsus, an attempt is made to generalize the Renaissance conception of man. Special attention is paid to the influence magic and alchemy upon the philosophy of the period. The inference is made, that mysticism as well as magic has meant by itself no so much the end of anthropocentric humanism, but rather its enlargement by new forms.